Las Reformas tributarias y su influencia en las importaciones y exportaciones en Colombia(1982-2014) (2020)
The purpose of this work was to make known the influence of the tax reforms, determining the incentives created in each reform and how they influenced the economy, imports and exports of Colombia, thus considering the hypothesis that is fulfilled since that the incentives created within the laws in the tax reforms for the promotion of imports and exports in Colombia were not efficient, in the period of 1982-2014, this is reflected during the work evidencing a depreciation of exports from Colombia this due that the administrations of these periods focused on increasing taxes and not on redistributing resources correctly, and thus created an uncertainty for investment. The purpose of this work is to generate criteria analyzing various factors that are reflected in new reforms to boost imports and exports in Colombia more efficiently.